2006
DOI: 10.1021/ja056343k
|View full text |Cite
|
Sign up to set email alerts
|

Models of the Membrane-Bound Cytochromes:  Mössbauer Spectra of Crystalline Low-Spin Ferriheme Complexes Having Axial Ligand Plane Dihedral Angles Ranging from 0° to 90°

Abstract: Crystalline samples of four low-spin Fe(III) octaalkyltetraphenylporphyrinate and two low-spin Fe (III) tetramesitylporphyrinate complexes, all of which are models of the bis-histidine-coordinated cytochromes of mitochondrial complexes II, III and IV, and chloroplast complex b 6 f, and whose molecular structures and EPR spectra have been reported previously, have been investigated in detail by Mössbauer spectroscopy. Of these, the first three have been shown to exhibit normal rhombic EPR spectra with three cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 107 publications
(385 reference statements)
1
25
0
Order By: Relevance
“…However, for His/Met ligated systems, no clear–cut links have been found between ligand-field parameters and axial groups’ orientations. In fact, looking at the NMR and EPR results shown in Table 3, there is no direct relationship between the presence of axial Met dynamics and observation of axial EPR spectra, nor between Met orientation (A, B) (Figure 8) and g –tensor parameters, in contrast with cytochromes with bis–His axial ligation for which ligand orientation and g –tensor parameters are clearly correlated 93,94. On the other hand, as shown in Figure 11, a linear correlation stands between the observed g max values (or their derived ligand–field anisotropy, V/Δ ratio) versus the averaged heme methyl chemical shift <δ> that can also accommodate the values taken from some other cytochromes c with His-Met axial ligation.…”
Section: Modulation Of the Heme Anisotropy Through Site–directed Mutamentioning
confidence: 96%
“…However, for His/Met ligated systems, no clear–cut links have been found between ligand-field parameters and axial groups’ orientations. In fact, looking at the NMR and EPR results shown in Table 3, there is no direct relationship between the presence of axial Met dynamics and observation of axial EPR spectra, nor between Met orientation (A, B) (Figure 8) and g –tensor parameters, in contrast with cytochromes with bis–His axial ligation for which ligand orientation and g –tensor parameters are clearly correlated 93,94. On the other hand, as shown in Figure 11, a linear correlation stands between the observed g max values (or their derived ligand–field anisotropy, V/Δ ratio) versus the averaged heme methyl chemical shift <δ> that can also accommodate the values taken from some other cytochromes c with His-Met axial ligation.…”
Section: Modulation Of the Heme Anisotropy Through Site–directed Mutamentioning
confidence: 96%
“…The two histidine ligands coordinating the heme iron in these systems are both orthogonal to the heme plane. When the two axial ligands lie in perpendicular planes the HALS EPR signal is observed, and if the axial ligands adopt a parallel orientation, the resulting EPR signal is much more rhombic 39,40. From these studies, correlation of structure with the observed electronic properties of the heme group shows that the presence of strong axial ligands (strong σ-donors and weak π -acceptors), a highly saddled-shaped heme plane, and/or electron withdrawing substituents at the meso positions of the porphyrin cause the heme configuration to be stabilized towards the axial (d xy ) 2 (d xz ,d yz ) 3 state.…”
Section: Introductionmentioning
confidence: 99%
“…Very bulky ligands and the use of picket fence porphyrin gave complexes with relative perpendicular orientations in iron(II) species [62,66]. Additional iron(II) and iron(III) studies are detailed in references [61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%